Emerging Perspectives on Akachi Adimora-Ezeigbo - Sackeyfio, Rose A.; Diala-Ogamba, Blessing (Lexington Books, 2017)
Emerging Perspectives on Akachi Adimora-Ezeigbo is a collection of 15 critical essays that highlights the literary contributions of Akachi Adimora-Ezeigbo as one of Nigeria’s leading female writers. The book includes a literary biography, professional profile, and an interview with professor Adimora-Ezeigbo that offers valuable insight into her life and works. Contributing scholars provide critical and theoretical perspectives on Adimora-Ezeigbo’s ouvre that represents a postcolonial lens to interpret the African world. Emerging Perspectives contextualizes Adimora-Ezeigbo’s works of fiction, poetry, and drama within African, Nigerian, and Women’s literary tradition. This collection builds upon critical and theoretical scholarship on leading African writers whose works comprise a dynamic and compelling genre of African writing that spans the post-independence era into the 21st century. The essays examine themes from Adimora-Ezeigbo’s writing such as patriarchy, feminism, war, cultural traditions, and contemporary issues in Nigerian society such as trafficking, and many of the social, economic, and political challenges to Nigeria’s development as a modern nation state.